Effect of Basil Seed Extract (Ocimum basillicum L) on Salmonella Typhi Growth Inhibition - Atika Putri Salsabilah; Budianto, Nugroho Eko Wirawan; Yunitati Maria Margaretha Sutandio (Universitas Wijaya Kusuma Surabaya, 2026)
Background: Basil seeds are a traditional spice with the name Ocimum basalicum L. Basil seed extract contains secondary metabolite compounds such as alkaloids, flavonoids and polyphenols which have the potential to act as antibacterials for Salmonella typhi. The aim of this research was to determine the antibacterial effectiveness of basil seed extract (Ocimum basalicum L) against the growth of Salmonella typhi bacteria. Objective: the aim of the research. Methods: The experimental research method was a post test only control group design using the well diffusion method. Result: The research results showed that the diameter of the inhibition zone formed at successive concentrations of 10%, 20%, 40% and 80% was 27.5 mm, 30.3 mm, 35.6 mm, 40.7 mm against Salmonella typhi. In the One-way Anova test, a p value of 0.000 <0.05 was obtained for the inhibition of the growth of Salmonella typhi bacteria. Conclusion: There is a potential anti-microbial effect of Salmonella typhi bacteria with an optimal concentration of 80%.